General approach to a solution of a problem of the analysis and synthesis of parameters of radar information fields - Нестеров, А. В. (Proceedings of National Aviation University (archive), 2000)
Considered is the concept of radar information field (RTF) and the system of parameters of quality RIF is indicated. The general approach to problems of the analysis and synthesis of parameters RIF is considered, the scheme on systematization of statement of such problems are offered, the features for want of their solution are marked